2015
DOI: 10.1007/s11192-015-1806-0
|View full text |Cite
|
Sign up to set email alerts
|

Scientific collaboration and high-technology exchanges among BRICS and G-7 countries

Abstract: Over the last two decades, emerging countries located outside North America and Europe have reshaped the global economy. These countries are also increasing their share of the world's scientific output. This paper analyzes the evolution of BRICS (Brazil, Russia, India, China and South Africa) and G-7 countries' international scientific collaboration, and compares it with high-technology economic exchanges between 1995-1997 and 2010-2012. Our results show that BRICS scientific activities are enhanced by their h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…China appears in the second period of our analysis, increasing its output in research on JIFs in the last two periods. This development is in line with the overall growth of the number of scientific publications from China (Moed, 2002;Bouabid et al, 2016). And although based on somewhat lower numbers of publications, the citation impact of some of the countries publishing on JIFs stand out, in particular of the Netherlands, Canada, and Australia.…”
Section: Resultssupporting
confidence: 65%
“…China appears in the second period of our analysis, increasing its output in research on JIFs in the last two periods. This development is in line with the overall growth of the number of scientific publications from China (Moed, 2002;Bouabid et al, 2016). And although based on somewhat lower numbers of publications, the citation impact of some of the countries publishing on JIFs stand out, in particular of the Netherlands, Canada, and Australia.…”
Section: Resultssupporting
confidence: 65%
“…The region of Central America and The Caribbean was not completely unknown to the professionals, as scientometricians have published important, but mainly specialised articles on topics like Cuban or Colombian publications in databases (Ruiz et al 2005;Anduckia et al 2000), scientometric analysis of certain subject fields (Torricella-Morales et al 2000;Macias-Chapula et al 1999;Guzman et al 1998;Wainer et al 2009) and even the dynamics of research profiles (Requena 2005), but a broader, comparative overview of the region has remained relatively unrevealed till these days. Traditionally more attention was paid to larger countries in South America, e.g., Brazil (Glänzel et al 2006;Leta et al 2006) or in the context of research in BRICS countries (Zitt et al 2006;Bouabid et al 2016). However, specific indicators such as publication potential and co-authorship patterns have been studied along with other scientometric indicators in the context socio-economic context as early as in 1992 (Schubert and Braun 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that the trends of intra-BRICS collaboration remained stable over time (Finardi, 2015). However, Bouabid et al (2016) found that both the intra-BRICS high-technology flows and the intra-BRICS scientific collaboration have remained very weak. Finally, He and Maskus (2012) developed a theoretical framework for "reverse" knowledge spillovers from developing to industrialized countries through FDI, although there are no empirical studies.…”
Section: Impact Of International Student and Scholar Mobility Andmentioning
confidence: 99%